ANALISIS KEPUTUSAN MENGGUNAKAN METODE CUT OFF POINT DAN FUZZY SIMPLE ADDITIVE WEIGHTING DALAM MENENTUKAN JENIS LAPTOPTERBAIK PADA MAHASISWA MATEMATIKA FMIPA UNIVERSITAS NEGERI PADANG - Avea Kristerima Gulo; Dewi Murni (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The emergence of various types and brands in the laptop industry poses problems for consumers in determining the best type of laptop. To assist consumers in determining the best type of laptop, a Decision Support System is needed. This research is an applied research. The data used is primary data obtained from the distribution of questionnaires through Google Form to students of the Department of Mathematics UNP batch of 2020, 2021, 2022. The variables used are Brand, Operating System, Processor, Solid State Drive, Random Access Memory, Battery, Screen Size, Laptop Weight, Color, Price. The methods used in this study are the Cut Off Point Method and the Simple Additive Weighting method. Based on the results of the problem analysis in determining the best laptop type using the Cut Off Point and Fuzzy Simple Additive Weighting methods, it shows that the Asus zenBook Pro laptop type is recommended as the best type of laptop with a preference value of 0.87